2004
DOI: 10.1002/adsc.200404055
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomerically Pure Cyclopropane Building Blocks: Synthesis and Transformations of 2‐Iodocyclopropylboronic Esters

Abstract: Dedicated to Joe P. Richmond on the occasion of his 60 th birthday.Abstract: Enantiomerically pure 2-iodocyclopropylboronic esters 6 and 8 have been synthesized from the readily available allylic alcohol 2 via an oxidation-radical decarboxylation sequence. These unique building blocks have been demonstrated to be versatile intermediates for a consecutive Suzuki-coupling with aryl-, heteroaryl-, alkenyl-, and cyclopropylboron derivatives (1 example each).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 38 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…A bulky chiral auxiliary at boron efficiently suppressed homocoupling of trans - 739 , allowing for selective cross-coupling between the cyclopropyl iodide and external boronic acid to give the corresponding products 740 in good yields. Remarkably, cis - 739 reacted readily as well, providing the corresponding cyclopropylboronic ester 741 (Scheme ) . The obtained boronic esters 740 and 741 can further be utilized as nucleophilic components in the second Suzuki−Miyaura cross-coupling reaction or in other stereoselective transformations of cyclopropyl boronates, such as oxidation into cyclopropanols or Matteson homologation. ,,
243
…”
Section: 14 Suzuki−miyaura Cross-couplingmentioning
confidence: 98%
“…A bulky chiral auxiliary at boron efficiently suppressed homocoupling of trans - 739 , allowing for selective cross-coupling between the cyclopropyl iodide and external boronic acid to give the corresponding products 740 in good yields. Remarkably, cis - 739 reacted readily as well, providing the corresponding cyclopropylboronic ester 741 (Scheme ) . The obtained boronic esters 740 and 741 can further be utilized as nucleophilic components in the second Suzuki−Miyaura cross-coupling reaction or in other stereoselective transformations of cyclopropyl boronates, such as oxidation into cyclopropanols or Matteson homologation. ,,
243
…”
Section: 14 Suzuki−miyaura Cross-couplingmentioning
confidence: 98%
“…[44] Following this report, the Suzuki-Miyaura coupling between cyclopropyl iodides and cyclopropyl boronates was used to elaborate contiguous cycloA C H T U N G T R E N N U N G propane arrays, [45] whereas 2-iodocyclopropylboronates were identified as useful building blocks for the preparation of 1,2-disubstituted cyclopropanes. [46] Additionally, industrial researchers reported the use of a Negishi coupling between ethyl cis-2-iodocyclopropanecarboxylate and an arylzinc A C H T U N G T R E N N U N G reagent as a key step in the process development of the non-nucleoside reverse transcriptase inhibitor MIV-150. [47] To further expand the scope of palladium-catalyzed reactions involving functionalized iodocyclopropanes, we investigated the feasibility of Sonogashira cross-couplings.…”
Section: Resultsmentioning
confidence: 99%
“… Additionally, prefunctionalization of the acid with an alkyl chloroformate and CDI proved to be useful . Other successful esterification techniques include the use of pyrithione derivatives, such as 305 , , 306 , and disulfide dipyrithione 307 (in combination with tributylphosphine) . The purity of reagent 305 was found to have a profound effect on the reaction yield …”
Section: Pioneering and Classical Methodsmentioning
confidence: 99%